De kunst van het provoceren. : Het activistisch kunstrepertoire van Luuks in Maastricht versus het artistieke actierepertoire van Provo in Amsterdam - Kalsbeek, Tessa (Publications de la Société Historique et Archéologique dans le Limbourg, 2024)
The art of provocation. The artistic action repertoire of Provo in Amsterdam (1965-1967) in relation to the activist art repertoire of Luuks in Maastricht (1966-1967)This article delves into Provo in Amsterdam (1965-1967) and Luuks in Maastricht (1966-1967) and offers an analysis of their action repertoires. It explores the core messages and creative expressions that defined the movements within the urban contexts of their cities.Provo, primarily a protest movement, aimed to provoke society in a creative manner. It attacked authority, critiqued urban planning, and expressed dissatisfaction with Claus van Amsberg through artistic protest actions. Luuks, on the other hand, was a collective of artists focused more on provoking the establishment through activist art. Rather than adhering to traditional politics, they developed an activist art repertoire.This study examines both Provo and Luuks through their magazines, happenings, and design, highlighting their shared core messages. Both movements opposed the monarchy, authority figures, and the capitalist consumer society. Provo mostly used language and wordplay in its expressions, while Luuks favored playful design and ludic games, all with a distinct sense of humor.While these movements were not uniform protest groups, this research identifies recurring ideas and how they were spread through recognizable repertoires. It sheds light on a lesser-explored period in Limburg’s history, emphasizing sociocultural dynamism beyond Amsterdam. During the 1960s, youngsters from diverse backgrounds came together, challenging societal norms and redefining politics with creativity and self-expression.This exploration of Provo and Luuks offers insight into an era when youth reshaped politics and culture, highlighting the interplay between art and politics in their actions. Future research could further explore audience reception of the repertoires of both movements.